ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦å¸ˆèŒƒå¦é™¢ä¸æ–‡ä¸“ä¸š2014å±Šå¦ç”Ÿ ä½¿ç”¨ä»‹è¯â€œå¾€ã€å‘ã€æœâ€çš„åè¯¯åˆ†æž - Oktaviani, Lina Try (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
æ‘˜è¦ ä»‹è¯æ˜¯è¯æ³•é‡Œé¢çš„é‡è¦éƒ¨åˆ†ï¼Œå…¶ä¸æ˜¯ä»‹è¯â€œå¾€â€ã€â€œå‘â€ã€ä¸Žâ€œæœâ€çš„ç”¨æ³•çš„å°¤ä¸ºå¤æ‚ï¼Œå®ƒæ˜¯å¯¹å¤–æ±‰è¯æ•™å¦ä¸çš„ä¸€ä¸ªè¯æ³•é‡ç‚¹ã€‚å› ä¸ºä»‹è¯â€œå¾€â€ã€â€œå‘â€ä¸Žâ€œæœâ€æœ‰å…±åŒç‚¹å’Œä¸åŒç‚¹ã€‚æœ¬è®ºæ–‡ç ”ç©¶çš„ç›®çš„æ˜¯ä½¿æ±‰è¯å¦ä¹ è€…ï¼Œå°¤å…¶æ˜¯ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦å¸ˆèŒƒæ•™è‚²å¦é™¢ä¸æ–‡ç³»çš„å¦ç”Ÿèƒ½å¤Ÿæ›´å¥½åœ°æŽŒæ¡ä»‹è¯â€œå¾€â€ã€â€œå‘â€ã€â€œæœâ€çš„ç”¨æ³•ï¼Œæé«˜å¯¹å¤–æ±‰è¯çš„æ•™å¦æ•ˆçŽ‡ï¼Œä»Žè€Œä½¿å¦ç”Ÿèƒ½å¤Ÿæ›´ä¸ºç†Ÿç»ƒåœ°æŽŒæ¡æ±‰è¯è¯æ³•ã€‚ä¸ºäº†è¾¾åˆ°è¿™ä¸€ç›®æ ‡ï¼Œç¬”è€…è°ƒæŸ¥ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦å¸ˆèŒƒæ•™è‚²å¦é™¢æ±‰è¯ä¸“ä¸š2014å±Šå¦ç”Ÿï¼Œè€ƒå¯Ÿä»–ä»¬å¦ä¹ ä»‹è¯ â€œå¾€ã€å‘ã€æœâ€çš„ä½¿ç”¨åè¯¯è¿›è¡Œäº†åˆ†æžã€‚å¦å¤–ä¹Ÿå‘çŽ°å¸¸è§åè¯¯ç±»åž‹ï¼Œå¹¶æ·±ç©¶å‡ºçŽ°è¿™äº›åè¯¯çš„åŽŸå› ï¼Œè¿›è€Œé’ˆå¯¹è¿™äº›é—®é¢˜æå‡ºå‡ ç‚¹æ•™å¦å¯¹è±¡ã€‚ Â å…³é”®è¯ï¼šÂ Â ä»‹è¯ â€œå¾€ã€å‘ã€æœâ€ Â Â Â Â Â Â Â åè¯¯åˆ†æžÂ Â Â Â Â Â Â Â Â Â Â Â Â åè¯¯åŽŸå› Â Abstract As for learning and teaching language, grammar is very important. Prepositions are an important part of grammar, Including methods of using preposition â€œwangâ€ , â€œxiangâ€ and â€œchaoâ€ usage is particularly complex. It is the main point in Chinese language teaching for foreigners, also one difficult grammar for learning to study. Because the preposition â€œwangâ€ , â€œxiangâ€ and â€œchaoâ€ have in common and different points. This research was conducted for Chinese language learners, especially the students of Chinese Language Departement Tanjungpura University to make them effectively master use of prepositions â€œwangâ€ , â€œxiangâ€ and â€œchaoâ€ to improve learning Chinese language efficiency among foreigners, the rate of increase for Chinese teaching, thus the students are proficient with the grammar of Chinese language. For achieved the objective, The writer surveyed the students of 2014 class in Chinese Language Departement Tanjungpura University errors in using prepositions â€œwangâ€ , â€œxiangâ€ and â€œchaoâ€. In addition also discover the summarize commonly seen types of mistakes, investigate the causes of errors, and after that confront them to raise countermeasures. Â Â Key Words : preposition â€œwangâ€ , â€œxiangâ€ and â€œchaoâ€ Error Analysis Causes of errors Â